Specialisation and spatial concentration in the economy of a Europe of the regions - Möller, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The subject of the paper is to analyse the development of the economic structure of regions and the concentration of economic activities in space. An important non-linearity obtained from new regional economics is stressed: the importance of the core increases at the early stage of the development, but then declines again. A similar pattern can be derived for specialisation. Against this background a discussion follows on whether specialisation trends will change after the completion of European Economic and Monetary Union and what would be the consequences. Finally, we present an empirical analysis of the prevailing trends with respect to regional concentration and specialisation for western Germany.
Keywords: Article